2015
DOI: 10.1111/jvim.13598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Iron Deficiency Using Reticulocyte Indices in Dogs Enrolled in a Blood Donor Program

Abstract: BackgroundPeople donating blood more than twice annually are at risk of developing iron deficiency. Little is known about the iron status of dogs enrolled in blood donor programs.HypothesisDogs donating blood ≥6 times annually will show evidence of iron deficiency based on their reticulocyte indices.AnimalsThirteen dogs enrolled in a blood donor program donating ≥6 times over the preceding 12 months and 20 healthy nondonor control dogs.MethodsProspective observational study. Mature red blood cell (RBC) indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Iron-deficient erythropoiesis is common among human blood donors and has also been documented in canine blood donors. 15,16 Iron deficiency in feline blood donors has not yet been documented but is suspected to occur. Enteral or parenteral iron supplementation is recommended for cats and dogs with evidence of iron deficiency and for iron-deficient human blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…Iron-deficient erythropoiesis is common among human blood donors and has also been documented in canine blood donors. 15,16 Iron deficiency in feline blood donors has not yet been documented but is suspected to occur. Enteral or parenteral iron supplementation is recommended for cats and dogs with evidence of iron deficiency and for iron-deficient human blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…Reticulocyte size and hemoglobin content can be measured in whole blood by some hematology analyzers. These reticulocyte indices, particularly decreased reticulocyte hemoglobin content (CHr), can be useful for the early detection of iron‐restricted erythropoiesis in a predisposed patient, but they are not as useful for distinguishing the mechanism of iron restriction 2,8–17 . Serum ferritin is expected to be low in absolute iron deficiency but normal to increased with iron sequestration; however, the assay is not widely available and can be difficult to interpret in animals that have both absolute iron deficiency and inflammatory disease 1 .…”
Section: Introductionmentioning
confidence: 99%
“…These reticulocyte indices, particularly decreased reticulocyte hemoglobin content (CHr), can be useful for the early detection of iron-restricted erythropoiesis in a predisposed patient, but they are not as useful for distinguishing the mechanism of iron restriction. 2,[8][9][10][11][12][13][14][15][16][17] Serum ferritin is expected to be low in absolute iron deficiency but normal to increased with iron sequestration; however, the assay is not widely available and can be difficult to interpret in animals that have both absolute iron deficiency and inflammatory disease. 1 Soluble transferrin receptor measurement may aid in distinguishing causes of iron-restricted erythropoiesis in humans, but a recent study indicated that the assay was not useful in dogs.…”
mentioning
confidence: 99%
“…Iron‐restricted erythropoiesis is defined as inadequate iron delivery to red cell precursors in the bone marrow, which impairs hemoglobin synthesis and can lead to anemia. Iron‐restricted erythropoiesis can be caused by absolute iron deficiency, iron sequestration, and functional iron deficiency 1‐14 . Absolute iron deficiency is a decrease in total body iron, which in dogs is often due to chronic external blood loss, but could also occur in animals fed diets deficient in iron 4,11,13 .…”
Section: Introductionmentioning
confidence: 99%